2021
DOI: 10.20344/amp.13181
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine Use in Opioid Maintenance Treatment Programme: Risks and Clinical Outcomes

Abstract: Introduction: The co-association of benzodiazepines and opioids is associated with an increased risk of overdose, death, and poorer psychosocial prognosis. The aim of this study is to characterize the prevalence, pattern of use, and primary clinical outcomes in benzodiazepines users in a public opioid maintenance treatment unit.Material and Methods: We conducted a cross-sectional study involving 236 patients treated with opioid substitutes (methadone and buprenorphine). We conducted a descriptive, bivariable, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…13 However, because this pharmacological group is dependent on the duration of treatment, it was excluded from this analysis. The same methodology has been applied to some widely prescribed benzodiazepines 65 that are dose-dependent PIM, suggesting that the results presented here may have been underestimated and there is a chance that the number of PIMs prescribed to older adults could be larger than reported in this study. Another limitation is related to the fact that the data available in this database do not allow for the correlation of the possibility of the use of PIMs being associated with a certain pathology or with the occurrence of a certain adverse drug reactions.…”
Section: Discussionmentioning
confidence: 92%
“…13 However, because this pharmacological group is dependent on the duration of treatment, it was excluded from this analysis. The same methodology has been applied to some widely prescribed benzodiazepines 65 that are dose-dependent PIM, suggesting that the results presented here may have been underestimated and there is a chance that the number of PIMs prescribed to older adults could be larger than reported in this study. Another limitation is related to the fact that the data available in this database do not allow for the correlation of the possibility of the use of PIMs being associated with a certain pathology or with the occurrence of a certain adverse drug reactions.…”
Section: Discussionmentioning
confidence: 92%
“…4 This risk is greatly heightened when taken with other medications that cause respiratory depression such as opioids. [5][6][7][8][9] Benzodiazepines have been the focus of research related to the harm of coprescribing sedatives and opioids, but it is important to note that all three classes of sedative hypnotics…”
Section: Introductionmentioning
confidence: 99%
“…For example, BZD use and misuse is more common among women than men (26,35), whites than other racial/ethnic groups (36), and among injection opioid users (26,37); notably, the latter two factors are correlated, as some prior research has found opioid injectors are more likely to be white than black (38)(39)(40). Finally, several types of comorbidities can potentially modulate BZD/opioid use including anxiety-related symptoms/diagnoses (41)(42)(43), and sleep problems (9,44,45). A common assumption is that exaggerated negative affect plays a pivotal role in motivating BZD use to "self-medicate" anxious or depressive symptoms [i.e., negative reinforcement; (46)], however, this may not be the only functional relationship between psychiatric conditions and the reinforcing effects of BZDs.…”
Section: Introductionmentioning
confidence: 99%